A superação dos conceitos positivo e negativo de liberdade pela dogmática jurídica constitucional: uma adequação jurídica do conceito de liberdade - Chamberlain, Marise Medeiros Cavalcanti (2005)
Trying to attest the importance that the liberty concept still have in the juridical dogmatic, this assignment is addressed to the overcome of the positive and negative concepts of liberty, since the first is founded in the consideration of liberty as a choice and the second conceives it like an unobstructed act. Initially, it’s brought off the political-philosophical route responsible for the comprehension of liberty in the juridical world, to later prove the inadequacy of the concept built under the basis of liberalism, chiefly of its dichotomization, to the determining categories of the knowledge in the juridical world. In this need, it’s configured the opacity produced by the dichotomization of the concept of liberty, mainly when attributed to it, such as norm’s contents, a negative dimension. The perplexity is touchy accentued by virtue of the exteriority and the rationality that characterize the right and don’t allow a concept of liberty that separates the act of the choices. First because the human conducts is an activity that qualifies the choices and if these remain in the inner place, they can’t be object of regulation of conducts. Second, because rationality, responsible by the determination of wanting-acting, is the attribute that distinguishes man from other beings. Individual and collective choices must be compatibilized by right because they’re the true expression of liberty and when taken in an autonomous form, with an ample number of options, whose making concrete is assured by the removal of impediments, you’re in front of the true realization of liberty. Therefore, there is no way how to conceive liberty in the ambit of disentailed actions of wantings, principally because the impediments and obstacles are identified from a valoured consideration tending to taking position in relation to purposes, choices, at last, of judgements that are determinative from valoures shared in society, which also say as regards of what concern the individual in his private sphere and to community, factor of accentued relevancy in the concept’s construction of liberty and determining in the conflict’s elucidation between liberties and between them and the second and third generation’s right.